2000
DOI: 10.1590/s0036-46652000000500001
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of BALB/c mice with Lacazia loboi

Abstract: In a previous study, the authors inoculated Swiss mice with Lacazia loboi (L. loboi) and succeeded in maintaining a granulomatous infiltrate and viable fungal cells up to one year and six months after inoculation. Considering the experimental work on paracoccidioidomycosis, 0.03 ml of a fungal suspension obtained from a biopsy of a Jorge Lobo's Disease patient were inoculated into both hind foot pads of 32 six week-old BALB/c mice of both sexes. The animals were sacrificed 1, 4, 7 and 10 months post inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 3 publications
2
17
0
1
Order By: Relevance
“…The recent discovery of an animal host was instrumental to maintaining in the laboratory several isolates of L. loboi for DNA extraction (14,19). We took advantage of this to maintain a permanent supply of L. loboi genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of an animal host was instrumental to maintaining in the laboratory several isolates of L. loboi for DNA extraction (14,19). We took advantage of this to maintain a permanent supply of L. loboi genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal suspension: L. loboi was obtained from the footpads of BALB/c mice previously inoculated for maintenance of the strain 14 . The animals were sacrificed 10 months post-inoculation and the hind footpads were removed and macerated in sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…However, the development of an experimental model of Jorge Lobo's disease in BALB/c mice, which show histological alterations similar to the human disease with a large number of viable fungi 14 , has contributed to the study of this mycosis.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, very little is understood about the conditions under which the pathogen grows and thrives, as well as its source and transmission route (Wiersema & Niemel 1965, Pang et al 2004, Lupi et al 2005, Paniz-Mondolfi et al 2007). Experimental inoculation attempts have been made using guinea pigs (Wiersema & Niemel 1965), hamsters (Wiersema & Niemel 1965, Opromolla & Noguiera 2000, tortoises (Geochelone denticulate, G. carbonaria and Kinosternon scorpioides; Sampaio et al 1971), monkeys (Macacca mulatta, M. nemestrina and M. fascicularis; Caldwell et al 1975), armadillos Euphractus sexcinctus (Sampaio & Braga-Dias 1977) and mice (Wiersema & Niemel 1965, Caldwell et al 1975, Opromolla et al 1999, Madeira et al 2000, 2003, Belone et al 2003, but many of those attempts yielded only short-term data on the development of the disease. Opromolla et al (1999) were able to successfully inoculate a Swiss strain of mice with lacaziosis and follow disease progression up to 18 mo post-inoculation; however, clinical presentation of the disease did not occur, and very few fungal cells were active by the end of the study.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Opromolla et al (1999) were able to successfully inoculate a Swiss strain of mice with lacaziosis and follow disease progression up to 18 mo post-inoculation; however, clinical presentation of the disease did not occur, and very few fungal cells were active by the end of the study. Other studies have demonstrated that BALB/c mice may be a suitable animal model for studying the infectivity and aggression of the lacaziosis pathogen, as infection was sustained and lesions developed post-inoculation; however, all of the BALB/c inoculation studies maintained infection for a maximum of 18 mo before the animals were sacrificed, thereby supplying limited short-term data on the progression of lacaziosis (Madeira et al 2000, 2003, Belone et al 2003. To our knowledge, there are no published reports of long-term studies that calculate a rate of lacaziosis progression in dolphins or other animals; therefore, very little is known about the quantitative proliferation of Lacazia loboi.…”
mentioning
confidence: 99%